2015
DOI: 10.1186/s40621-015-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Economic development and road traffic fatalities in Russia: analysis of federal regions 2004–2011

Abstract: BackgroundThe relationship between economic development and road safety at sub-national level has not been well established. This study aims to assess the relationships between economic growth (measured by gross regional product (GRP)) and road traffic fatalities (RTFs) and crash fatality ratio (CFR) at sub-national level in Russia.MethodsWe used published secondary data on annual RTFs and CFR obtained from the traffic police and socioeconomic development indicators from the statistics department for each Russ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…High GNI was an important factor in reducing pedestrian deaths in this study. This is because the increase in GNI increases the number of motor vehicles [16] and improves the construction of safer roads with signaled pedestrian crosswalks, humps, and road traffic cameras [17][18][19]. The increased vehicle per person ratio is associated with reduced pedestrian road users and their death rates.…”
Section: Discussionmentioning
confidence: 99%
“…High GNI was an important factor in reducing pedestrian deaths in this study. This is because the increase in GNI increases the number of motor vehicles [16] and improves the construction of safer roads with signaled pedestrian crosswalks, humps, and road traffic cameras [17][18][19]. The increased vehicle per person ratio is associated with reduced pedestrian road users and their death rates.…”
Section: Discussionmentioning
confidence: 99%
“…In a sub-national analysis, He et al found that the rates of road traffic fatalities decreased linearly with the economic growth [26]. They showed that there was a 0.69-point reduction in the number of fatalities per unit increase in gross regional product across 67 federal regions during 2004-2011.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that there was a 0.69-point reduction in the number of fatalities per unit increase in gross regional product across 67 federal regions during 2004-2011. It is worth mentioning that number of physicians partially explained the association between economic development and mortality due to traffic accidents [26].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence rate of traffic accidents in Iran has been 26.5 in 100.000 people per year (8). Noting that middle-income countries have the highest mortality rate caused by road traffic accidents (20.1 in 100.000) (9), vital importance to reduce mortality rate from the accidents in these countries so that total burden of the mortality rate reduces as well (9).…”
Section: Introductionmentioning
confidence: 99%